(500) days of summer - Webb, Marc; Neustadter, Scott; Weber, Michael H. (Screenwriter); Gordon-Levitt, Joseph, 1981-; Deschanel, Zooey, 1980-; Watermark (Production company) (United States : 20th Century Fox Home Entertainment, 2010)
Tom believes, even in this cynical modern world, in the notion of a transforming, cosmically destined, lightning-strikes-once kind of love. Summer doesn't. Not at all. But that doesn't stop Tom from going after her, again and again. The fuse is lit on Day 1--when Tom, a would-be architect turned sappy greeting card writer, encounters Summer, his boss's breezy, beautiful new secretary, fresh off the plane from Michigan. Though seemingly out of his league, Tom soon discovers he shares plenty in common with Summer. By Day 31, things are moving ahead, albeit 'casually.' By Day 32, Tom is irreparably smitten, living in a giddy, fantastical world of Summer on his mind. By Day 185, things are in serious limbo--but not without hope.
Special features: Lost days of summer. Deleted and extended scenes -- Digital copy transfer file.
Originally released as a motion picture in 2009.
Produced by Jessica Tuchinsky, Mark Waters, Mason Novick, Steven J. Wolfe ; costume designer Hope Hanafin ; music by Mychael Danna & Rob Simonsen ; Music supervisor Andrea von Foerster ; film editor Alan Edward Bell ; production designer Laura Fox ; director of photography Eric Steelberg.
Joseph Gordon-Levitt, Zooey Deschanel.
DVD; Aspect ratio 2.40:1; Widescreen 16:9; Dolby Digital 5.1.
English with optional English subtitle for the hearing impaired.
English closed caption.
Keywords: Dating (Social customs) -- United States -- Drama; Greeting cards industry -- United States -- Drama; Administrative assistants -- United States -- Drama; Brothers and sisters -- United States -- Drama; Feature films; Fiction films; Comedy films